Polymeric carbon nitride with internal n-p homojunctions for efficient photocatalytic CO₂ reduction coupled with cyclohexene oxidation - Zhen, Wenlong (2022)
We present the creation of internal n-p homojunctions in polymeric carbon nitride (PCN) by inserting phenyl groups, which bridge the adjacent tri-s-triazine moieties, into the PCN matrix through copolymerization methods. The linkage by the benzene rings results in a large π-conjugated structure and controllable electron-localization, allowing for modulating the electronic structure, optical properties, and lipophilicity of the prepared sample (CDT-DCDA-490). The electrochemical studies reveal the co-existence of both n-type and p-type domains in the polymeric skeleton of CDT-DCDA-490. The created internal n-p homojunctions can accelerate the separation and transfer kinetics of photogenerated charge carriers in the PCN matrix. As a result, the functionalized PCN photocatalyst showed excellent activities in the photocatalytic CO2 reduction and simultaneous olefin oxidation in the water-oil biphasic system, giving high selectivity for the production of CO and 2-cyclohexen-1-one. In addition, the CDT-DCDA-490 semiconductor also displays excellent PEC performance as photoanode. This work provides valuable guidance for future design and development of novel functional PCN-based photocatalysts with internal junctions for efficient solar fuels production.